Sustained deposition of contaminants from the Deepwater Horizon spill - Yan, Beizhan (Proc Natl Acad Sci U S A, 2016)
The 2010 Deepwater Horizon oil spill resulted in 1.6–2.6 × 10(10) grams of petrocarbon accumulation on the seafloor. Data from a deep sediment trap, deployed 7.4 km SW of the well between August 2010 and October 2011, disclose that the sinking of spill-associated substances, mediated by marine particles, especially phytoplankton, continued at least 5 mo following the capping of the well. In August/September 2010, an exceptionally large diatom bloom sedimentation event coincided with elevated sinking rates of oil-derived hydrocarbons, black carbon, and two key components of drilling mud, barium and olefins. Barium remained in the water column for months and even entered pelagic food webs. Both saturated and polycyclic aromatic hydrocarbon source indicators corroborate a predominant contribution of crude oil to the sinking hydrocarbons. Cosedimentation with diatoms accumulated contaminants that were dispersed in the water column and transported them downward, where they were concentrated into the upper centimeters of the seafloor, potentially leading to sustained impact on benthic ecosystems.